2012
DOI: 10.1086/665047
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Here and Now versus There and Later: The Moderating Role of Psychological Distance on Assortment Size Preferences

Abstract: Consumers prefer larger assortments, despite the negative consequences associated with choosing from these sets. This article examines the role of psychological distance (temporal and geographical) in consumers’ assortment size decisions and rectifies contradicting hypotheses produced by construal level theory. Six studies demonstrate that while consumers prefer larger assortments when the choice takes place in the here and now, they are more likely to prefer small assortments when choices pertain to distant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 51 publications
6
102
0
4
Order By: Relevance
“…Although we found no differences on this measure based on our manipulation (and thus no support for an influence of construal level), we wish to draw a theoretical connection here between mental accounting and construal-level theory more generally. Mental accounting involves changes in mental representation, as does construal-level theory (Day and Bartels 2008;Goodman and Malkoc 2012). Transactions can be considered in reference to general (abstract) accounts or in reference to specific (concrete) accounts.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found no differences on this measure based on our manipulation (and thus no support for an influence of construal level), we wish to draw a theoretical connection here between mental accounting and construal-level theory more generally. Mental accounting involves changes in mental representation, as does construal-level theory (Day and Bartels 2008;Goodman and Malkoc 2012). Transactions can be considered in reference to general (abstract) accounts or in reference to specific (concrete) accounts.…”
Section: Discussionmentioning
confidence: 99%
“…To test the manipulations, a separate test was performed in which 17 respondents (nine men) participated. The desirability versus feasibility focus of the advertising appeals was measured based on Goodman and Malkoc (2012); Lee, Keller, and Sternthal (2010); and Liberman and Trope (1998). Three items were used to measure the desirability of the ad: "These ads suggest that the product will give you a positive feeling," "These ads influence your emotions," and "These ads influence your feelings" (a Feasible D .92; a Desirable D .88).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in Goodman and Malkoc (2012), abstract processing prompts consumers to develop heightened perceptions of similarity among alternatives, as it leads to a focus on commonalities rather than distinctions among options (Förster, Liberman, and Kuschel 2008); prompts consumers to think in terms of overarching, shared themes rather than individuating factors (Malkoc, Zauberman, and Ulu 2005); and leads to a reliance on general rather than specific principles (Liberman, Trope, and Stephan 2007). By contrast, the low-level construal prompted by attribute-based sets should lead to a search for differentiation among items (Goodman and Malkoc 2012), leading to lowered perceptions of similarity among items in the set as a whole relative to that seen in benefit-based sets. On the basis of prior models of similarity perceptions (e.g., Tversky 1977), we propose that more abstract processing will enhance similarity perceptions at a global level, influencing perceptions of the assortment as a whole, such that: H2: Benefit-based organizations will lead to greater perceptions of assortment similarity than will attribute-based organizations.…”
Section: Implications Of Organization Type Formentioning
confidence: 99%
“…For example, in the case of a stock-out, heightened similarity perceptions may lower consumers' aversion to trading off one item for another (Novemsky and Kahneman 2005), meaning that their first-and secondchoice options are seen as similarly satisfying. Further, to the extent that individuals perceive items to be similar, they are more likely to see them as good substitutes for one another (Day, Shocker, and Srivastava 1979;Goodman and Malkoc 2012;Ratneshwar and Shocker 1991). Prior research has shown that in situations of horizontal differentiation, that is, where utility derived from the product and price are unrelated, greater perceived substitutability increases price sensitivity (e.g., Boulding, Lee, and Staelin 1994;Diehl, Kornish, and Lynch 2003;Kaul and Wittink 1995;Mitra and Lynch 1995).…”
Section: Effects Of Assortment Organization On Strength Of Preferencementioning
confidence: 99%